CULTURAL IDENTITY STEREOTYPES OF MADURESE WOMEN IN TRADITIONAL EXPRESSIONS - Moh Hafid Effendy; Saiful Hadi; Siti Azizah; Mochamad Arifin Alatas; Akhtem A. Dzhelilov (Universitas PGRI Sumatera Barat, 2026)
The phenomenon of stereotypes against Madurese women embedded in traditional expressions reflects profound tensions between entrenched cultural values, evolving social norms, and prescribed gender roles within the society. While Madurese culture is rich in oral traditions, previous studies have tended to focus on general cultural descriptions without critically examining the nuanced construction of female identity within these linguistic artifacts. Consequently, this study aims to explore how the cultural identity of Madurese women is systematically formed and reproduced through proverbs and investigates how specific stereotypes emerge and persist in everyday social practices. Employing a qualitative ethnographic approach, data were collected through in-depth interviews, participant observation, and textual analysis of specific proverbs related to character, moral values, social relations, and the domestic and public role of women. This method allowed for a deep exploration of the social, cultural, and historical contexts surrounding these expressions. The results of the study show that Madurese women are predominantly described as hardworking, resilient, and significantly contributing to the economy, yet they are simultaneously burdened with the heavy responsibility of maintaining the honor of the family. Traditional proverbs display a complex duality between genuine appreciation for women's vital roles and subtle social control over their morality. Thus, these expressions function as both a cultural reflection and a normative instrument in the ongoing construction of gender identity. These findings confirm that Madurese stereotypes of women are not static but are the result of continuous negotiations between tradition, structural patriarchy, and modern social change. Ultimately, this research provides new insights into the dynamics of gender identity in Madurese society, offering implications for understanding how language perpetuates or challenges gender inequalities in indigenous communities. Understanding these linguistic mechanisms is crucial for developing interventions that promote gender equity while respecting cultural heritage.